Chronic Venous Insufficiency with Varicose Diseases of the Lower Limb - Vasilevskiy E.A. (Genius Publishing Group, 2023)
The massive nature of varicose veins of the saphenous veins of the lower extremities and developing complications among the working population with loss of ability to work and disability determine the social and economic significance of the problem. The authors used lymphotropic therapy in the complex treatment of chronic venous insufficiency in 41 patients with varicose veins of the lower extremities. The effect on the lymphatic system of the lower extremities through LT and LS significantly improves microcirculation, creates favorable conditions for relieving symptoms of varicose veins of the saphenous veins, prevents the development of complications, both during conservative treatment and during surgical interventions, and promotes rapid rehabilitation of patients.
Keywords: Chronic venous insufficiency; varicose veins of the lower extremities; lymphotropic therapy